The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s12943-023-01755-5
|View full text |Cite
|
Sign up to set email alerts
|

CAR T-Cell therapy for the management of mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) is a subtype of Non-Hodgkin lymphoma (NHL) of mature B-cells characterized by translocation, which is typically due to excess expression of Cyclin D1. Although with the progress in our knowledge of the causes for MCL and available treatments for MCL, this cancer is still incurable. Age, male gender, rapid advancement, significant nodal involvement, elevated serum lactate dehydrogenase level, and prognostic indications including increased expression of Ki-67 and presence of TP53 mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 143 publications
0
16
0
Order By: Relevance
“…Megyesfalvi Z et al [30] found widespread inactivation of the TP53 gene in small cell lung cancer, suggesting potential e cacy of immunotherapy in this context. Chen et al [31] reported the rst case of CAR-T cell therapy in an LFS patient with hematological malignancy, suggesting that CAR-T cell therapy may be an alternative option compared to traditional chemotherapy and allogeneic hematopoietic stem cell transplantation. In our research, the CPS of PD-L1 in the proband 1 was 70%, and the patient received radical resection, postoperative chemotherapy combination with immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Megyesfalvi Z et al [30] found widespread inactivation of the TP53 gene in small cell lung cancer, suggesting potential e cacy of immunotherapy in this context. Chen et al [31] reported the rst case of CAR-T cell therapy in an LFS patient with hematological malignancy, suggesting that CAR-T cell therapy may be an alternative option compared to traditional chemotherapy and allogeneic hematopoietic stem cell transplantation. In our research, the CPS of PD-L1 in the proband 1 was 70%, and the patient received radical resection, postoperative chemotherapy combination with immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In an adjusted comparison using inverse probability weighting between ZUMA-2 and SCHOLAR-2, brexu-cel was associated with improved OS compared to non-CAR T cell standard of care (HR 0.38, 95% CI 0.23–0.61) [ 34 ]. Efficacy of CAR T cell therapy should be considered alongside potential class-specific toxicities, such as immunologic effector cell-associated cytokine release syndrome and neurotoxicity, among other potential constraints to successful CAR T cell therapy [ 35 ]. To our knowledge, pirtobrutinib has yet to be evaluated in the real-world setting; however, the therapy is currently undergoing phase 3 evaluation in the cBTKi-naive setting of MCL, with comparison to ibrutinib, acalabrutinib, or zanubrutinib (BRUIN MCL-321 trial; NCT04662255).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study across 15 international sites, in which 114 patients were enrolled, median OS after ibrutinib failure was only 2.9 months [ 26 ]. In this setting, promising results were recently obtained by chimeric antigen receptor (CAR) T-cells [ 27 , 28 ]. Brexucabtagene autoleucel is a CD19-directed CAR T-cell therapy approved for R/R MCL after two previous regimens; 189 cases who underwent leukapheresis were enrolled in a real-life study.…”
Section: Introductionmentioning
confidence: 99%
“…Brexucabtagene autoleucel is a CD19-directed CAR T-cell therapy approved for R/R MCL after two previous regimens; 189 cases who underwent leukapheresis were enrolled in a real-life study. ORR and CR were 90% and 82%, respectively, with an estimated 12-month PFS of 59% after a median follow-up of 14.3 months [ 27 , 28 ]. However, this approach is not consistently feasible, due to restrictive eligibility criteria, progressive disease (PD), or death while waiting for manufacturing [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation